In situ arsenic speciation at the soil/water interface of saline-alkaline lakes of the Pantanal, Brazil: A DGT-based approach - Viana, José Lucas Martins; Souza, Adriana Felix de; Hernández, Amauris Hechavarría; Elias, Lucas Pellegrini [UNESP]; Eismann, Carlos Eduardo [UNESP]; Rezende-Filho, Ary Tavares; Barbiero, Laurent; Menegario, Amauri Antonio [UNESP]; Fostier, Anne Hélène (Elsevier, 2022)
Arsenic (As) is a naturally occurring element in the Earth's crust, exhibiting toxicity towards a wide range of living organisms. Its properties and environmental dynamics are strongly regulated by its speciation, and the species As(III) and As(V) are the most commonly found in environmental systems. Recently, high concentrations of As were found in saline-alkaline lakes of the Pantanal (Brazil), which is the largest wetland area in the world. Therefore, we evaluated As contamination and its redox speciation (As(III) and As(V)) at the soil/water interface of biogeochemically distinct saline-alkaline lakes of Pantanal wetlands (Brazil). Both conventional sampling and in situ diffusive gradients in thin films (DGT) technique were employed. Zirconium oxide and 3-mercaptopropyl were used as ligand phases in DGT to selectively bind As species. High concentrations of total dissolved As in a shallow water table were found (<2337.5 μg L−1), whereas levels in soils were up to 2.4 μg g−1. Distinct scenarios were observed when comparing speciation analysis through spot sampling and DGT. Considering spot sampling, As(V) was the main species detected, whereas As(III) was only detected in only a few samples (<4.2 μg L−1). Conversely, results obtained by DGT showed that labile As(III) dominated arsenic speciation at the soil/water interface with levels up to 203.0 μg L−1. Coupling DGT data and DGT induced fluxes in sediments and soils model allowed obtaining kinetic data, showing that the soil barely participated in the arsenic dynamics on the shore of the lakes, and that this participation depends on the evapoconcentration process occurring in the region. Therefore, soil acts like a nonreactive matrix depending on the natural concentration process. In addition, our results reinforced the different geochemical characteristics of the studied saline-alkaline lakes and highlights the importance of robust passive sampling techniques in the context of metal/metalloid speciation in environmental analysis.
Keywords: Arsenic; Diffusive gradients in thin films; Pantanal; Speciation